Effects of crossed leg on blood pressure - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2004)
It is known that many factors influence an individual's blood pressure measurement. However, guidelines for accurately measuring blood pressure inconsistently specify that the patient should keep feet flat on the floor. The purpose of this study was to examine the effects of a crossed leg position on blood pressure in a Turkish sample. A prospective study of 238 subjects with an unmedicated high-normal blood pressure, stage 1 or stage 2 hypertension was conducted. After obtaining informed consent, subjects positioned their feet flat on the floor while their blood pressure was being measured. After 3 min, the blood pressure was measured again with the subject's leg crossed at the knee. Mean values of blood pressure were compared by t-test between two measurements. Statistical significance for all analysis was taken at the 5% level. The results indicated that both systolic and diastolic blood pressure increased significantly with the crossed leg position. Crossing the leg at the knee results in a significant increase in blood pressure. When blood pressure is measured, subjects should be instructed to have feet flat on the floor to eliminate a potential source of error.
Keywords: blood pressure; crossed leg; hypertension; POPULATION; IMPACT